Shorebirds: The Delaware Bay Connection (U.S. Fish and Wildlife Service, 2004)
This brochure gives information about migrating shore birds and the threats these birds face during their long journeys with stopovers in the Delaware Bay. Shorebirds have some of the longest migrations known, traveling from their wintering ground at the tip of South America to their Arctic breeding grounds and back again each year. Stopovers like Delaware Bay play an important role by providing food resources for these birds at critical times during migration. Among such migrating birds are Red Knot (Calidris canutus), Ruddy Turnstone (Arenaria interpres), Semipalmated Sandpiper (Calidris pusilla), and Sanderling (Calidris alba). The brochure also discusses horseshoe crabs (Limulus polyphemus) as shorebirds are especially dependent upon the horseshoe crab eggs for food. Ideas for a Fishery Management Plan for Birds and how everyone can help are put forth.